2016
DOI: 10.3920/bm2015.0075
|View full text |Cite
|
Sign up to set email alerts
|

Faecalibacterium prausnitzii phylotypes in type two diabetic, obese, and lean control subjects

Abstract: Faecalibacterium prausnitzii is one of the main butyrate producers in the healthy human gut. Information on its genetic diversity is lacking, although two genetic phylotypes have been differentiated. In the present study, F. prausnitzii phylotypes were examined in faeces of obese and type two diabetes with similar eating behaviour compared to a lean control group. The purpose of the study was to analyse if an excessive butyrate production induced by different F. prausnitzii phylotypes discriminates between obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 41 publications
3
42
1
Order By: Relevance
“…Functional differences between genetic phylotypes of F prausnitzii with different capacities for butyrate production have also been observed with lean individuals having a genetic variant with a more moderate capacity for butyrate production compared with individuals with obesity and T2D. 57 In accordance with this, children with obesity had higher stool concentrations of butyrate compared with normal-weight controls. 58 There are some limitations to our study, including a reduced generalizability of our findings because of the primarily white and middle to high socioeconomic status of our participants.…”
Section: Discussionmentioning
confidence: 71%
“…Functional differences between genetic phylotypes of F prausnitzii with different capacities for butyrate production have also been observed with lean individuals having a genetic variant with a more moderate capacity for butyrate production compared with individuals with obesity and T2D. 57 In accordance with this, children with obesity had higher stool concentrations of butyrate compared with normal-weight controls. 58 There are some limitations to our study, including a reduced generalizability of our findings because of the primarily white and middle to high socioeconomic status of our participants.…”
Section: Discussionmentioning
confidence: 71%
“…Literature data are conflicting about the level of F. prausnitzii in obesity, with studies showing positive (Balamarugan et al, 2010), negative (Borgo et al, 2016) or no association (Feng et al, 2014). These contradictory results may be due to experimental factors such as small cohort sizes or the use of different primer sets, or may be explained by the existence of multiple F. prausnitzii phylotypes (Louis et al, 2009;Hippe et al, 2016). Indeed, Hippe and colleagues (2016) suggested that the two identified phylotypes display different physiological properties and seem to produce different amounts of butyrate in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…No universal microbe has been identified leading to the difference in weight gain, but, in various studies, associations of weight gain with different individual bacterial taxa, including Akkermansia muciniphila , Faecalibacterium prausnitzii [14], [59], [60], [61] and Lactobacillus reuteri and Roseburia intestinalis [57] have been observed. Some of the complexity in determining cause and effect is illustrated by a recent study by Goodrich and colleagues [62b], which demonstrated a strong association of BMI in humans with microbiota of the Christensenellaceae family.…”
Section: Developing Murine Models To Study Gene/environment/microbiommentioning
confidence: 99%